Methacrylic resin, method for producing same, resin composition, coating material, and resin film
By increasing the molecular weight ratio and structural regularity of methacrylic resins, combined with appropriate polymerization conditions, the problems of insufficient heat resistance and thermal stability are solved, and the mechanical properties and chemical recycling are improved, and suitable for high temperatures and complex forming processes.
Patent Information
- Application Number
- CN202380044610.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-07
- Filing Date
- 2023-06-07
- Publication Date
- 2025-01-14
AI Technical Summary
The existing high molecular weight methacrylic resins have room for improvement in heat resistance and thermal stability, and the manufacturing of molded articles with excellent mechanical properties faces challenges.
Developed a methacrylic resin with a structural unit proportion of methyl methacrylate of more than 98%, a weight average molecular weight of more than 400,000, a molecular weight ratio of 1.6 to 2.8, and a homogeneous stereoregulation degree of 55%. As above, the 5% weight loss temperature reaches above 300°C, and the terminal double bond ratio is controlled to be less than 0.015 mol% by specific polymerization initiator and chain transfer agent ratio to improve thermal stability.
Methacrylic resins and molded bodies with excellent heat resistance and thermal stability are achieved, with excellent mechanical properties and chemical recycling properties, and are suitable for high-temperature applications and complex molding processes.
Smart Images

Figure BDA0005166523520000021 
Figure BDA0005166523520000041 
Figure BDA0005166523520000081
Abstract
Description
Technical Field
[0001] The present invention relates to a methacrylic resin and a method for producing the same, a resin composition, a coating and a resin film. Background Art
[0002] Methacrylic resins are widely used in various fields due to their excellent transparency, weather resistance, processability, etc. In particular, resin films obtained by molding methacrylic resins are also used for optical applications such as display devices due to their excellent optical properties.
[0003] As methods for producing resin films, the following are known: melt extrusion using a T-die; solution casting in which a coating obtained by dissolving a resin in a solvent is cast onto the surface of a support and the solvent is evaporated to form a film. Among them, the solution casting method has the advantages of being less likely to cause polymer orientation and isotropic strength or optical properties of the obtained resin film due to the small physical stress applied to the resin film during film formation. In addition, the solution casting method also has the advantage of extremely high thickness accuracy of the obtained resin film.
[0004] When a resin film is produced by a solution casting method, a methacrylic resin having a high molecular weight is generally used. By using a high molecular weight methacrylic resin, not only is the solution casting method suitable, but the mechanical properties of the obtained resin film are also improved.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2019 / 167471 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] However, the present inventors have found through research that such high molecular weight methacrylic resins still have room for improvement in terms of heat resistance and thermal stability.
[0010] The present invention aims to provide a methacrylic resin having excellent heat resistance and thermal stability and capable of producing a molded product having excellent mechanical properties, a method for producing the same, a resin composition and a coating containing the methacrylic resin, a resin film containing the methacrylic resin, and a polarizing plate and a display device obtained by using the resin film.
[0011] Solutions for solving problems
[0012] Specific means for solving the above-mentioned problems include the following embodiments.
[0013] <1> A methacrylic resin, wherein the ratio of structural units derived from methyl methacrylate is 98% by mass or more,
[0014] The weight average molecular weight (Mw) measured by gel permeation chromatography (GPC) is 400,000 or more, and the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) is 1.6 to 2.8,
[0015] The syndiotacticity expressed as triad is 55% or more,
[0016] 5% weight loss temperature is above 300℃,
[0017] The residual ratio of the chain transfer agent is 0.005 mass % or less.
[0018] <2> according to <1> The methacrylic resin contains a terminal structure represented by the following formula (1) derived from a polymerization initiator.
[0019]
[0020] (Where R 1 , R 2 and R 3 Each independently represents an alkyl group, a substituted alkyl group, an ester group or an amide group. 1 , R 2 and R 3 At least one of represents an ester group or an amide group. 1 , R 2 and R 3 The two of them may be bonded to each other to form an alicyclic structure. * represents a connecting bond to a structural unit derived from a monomer. )
[0021] <3> according to <1> or <2> The methacrylic resin has a terminal double bond whose ratio to the structural unit derived from methyl methacrylate is less than 0.015 mol %.
[0022] <4> according to <1> ~ <3> The methacrylic resin described in any one of the preceding claims has a glass transition temperature of 120° C. or higher.
[0023] <5> A method for producing a methacrylic resin, comprising:
[0024] A polymerization step of polymerizing a monomer mixture containing 98% by mass or more of methyl methacrylate at a temperature lower than 100° C. in the presence of a polymerization initiator and a chain transfer agent until a polymerization conversion rate reaches 90% or more and a residual rate of the chain transfer agent reaches 0.005% by mass or less,
[0025] The amount of the chain transfer agent used is 0.03 mol% or less relative to the total amount of the monomer mixture.
[0026] The ratio of the total molar amount of the chain transfer agent to the total molar amount of the polymerization initiator is 1.6 or less.
[0027] <6> according to <5> In the method for producing a methacrylic resin, the polymerization initiator is a non-nitrile azo polymerization initiator.
[0028] <7> according to <5> or <6> The method for producing a methacrylic resin comprises the step of performing aqueous polymerization in the polymerization step.
[0029] <8> A resin composition comprising <1> ~ <4> The methacrylic resin described above may contain multilayered polymer particles.
[0030] <9> A coating material for producing a thin film by solution casting, comprising <1> ~ <4> The methacrylic resin and solvent described in any one of the above,
[0031] The solvent includes a first solvent having a hydrogen bonding term δH of 1-12 in the Hansen solubility parameter and a second solvent having a hydrogen bonding term δH of 14-24.
[0032] <10> A resin film comprising <1> ~ <4> The methacrylic resin described above.
[0033] <11> according to <10> The resin film has a bending frequency of 6,000 or more until breaking in a clamshell bending test.
[0034] <12> according to <10> or <11> The resin film comprises multi-layered polymer particles.
[0035] <13> according to <10> ~ <12> The resin film according to any one of the preceding claims, wherein the resin film is a polarizer protective film.
[0036] <14> A polarizing plate is a polarizing plate <10> ~ <13> The resin films described above are stacked.
[0037] <15> A display device comprising <14> The polarizing plate.
[0038] Effects of the Invention
[0039] According to the present invention, there are provided a methacrylic resin having excellent heat resistance and thermal stability and capable of producing a molded product having excellent mechanical properties, a method for producing the same, a resin composition and a coating containing the methacrylic resin, a resin film containing the methacrylic resin, and a polarizing plate and a display device obtained by using the resin film. DETAILED DESCRIPTION
[0040] Hereinafter, specific embodiments obtained by applying the present invention will be described in detail. Unless otherwise specified, the symbol "to" indicating a numerical range is used to mean that the lower limit and the upper limit of the range are included.
[0041] <Methacrylic resin>
[0042] In the methacrylic resin described in the present embodiment, the proportion of the structural unit derived from methyl methacrylate is 98% by mass or more, and the proportion of the structural unit derived from the monomer other than methyl methacrylate is 2% by mass or less. In the methacrylic resin described in the present embodiment, the proportion of the structural unit derived from methyl methacrylate is preferably 99% by mass or more, and more preferably 100% by mass (i.e., homopolymer of methyl methacrylate). It should be noted that the structural unit derived from methyl methacrylate is represented by the following formula.
[0043]
[0044] Examples of monomers other than methyl methacrylate include alkyl acrylates such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate; aryl acrylates such as phenyl acrylate; cycloalkyl acrylates such as cyclohexyl acrylate and norbornyl acrylate; alkyl methacrylates other than methyl methacrylate such as ethyl methacrylate, propyl methacrylate, and butyl methacrylate; aryl methacrylates such as phenyl methacrylate; cycloalkyl methacrylates such as cyclohexyl methacrylate and norbornyl methacrylate; aromatic vinyl compounds such as styrene and α-methylstyrene; acrylamide; methacrylamide; acrylonitrile; methacrylonitrile, and the like.
[0045] The weight average molecular weight (Mw) of the methacrylic resin described in the present embodiment is 400,000 or more. If the weight average molecular weight (Mw) of the methacrylic resin is 400,000 or more, there is a tendency that the mechanical properties of the obtained molded body are improved, for example, a resin film with excellent bending resistance can be obtained. The weight average molecular weight (Mw) of the methacrylic resin is preferably 600,000 or more, more preferably 700,000 or more, and further preferably 800,000 or more. The upper limit of the weight average molecular weight (Mw) is not particularly limited, and from the viewpoint of moldability, it is preferably 2.5 million or less, more preferably 2 million or less, further preferably 1.5 million or less, and particularly preferably 1.2 million or less.
[0046] In addition, the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the methacrylic resin according to the present embodiment, i.e., the dispersion (Mw / Mn) is 1.6 to 2.8, preferably 1.7 to 2.5, more preferably 1.7 to 2.4, and further preferably 1.7 to 2.3. When the dispersion (Mw / Mn) of the methacrylic resin is 1.6 or more, the fluidity of the methacrylic resin tends to be improved and molding tends to be easy, and when the dispersion (Mw / Mn) of the methacrylic resin is 2.8 or less, the mechanical properties such as impact resistance, toughness, and bending resistance of the obtained molded body tend to be improved.
[0047] The weight average molecular weight (Mw) and number average molecular weight (Mn) in this specification are values calculated in terms of standard polystyrene measured by gel permeation chromatography (GPC), and are measured by the method described in the examples described later.
[0048] It should be noted that the weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin can be controlled by adjusting the type and amount of the polymerization initiator and chain transfer agent used in synthesizing the methacrylic resin.
[0049] In addition, the syndiotacticity (rr) of the methacrylic resin described in this embodiment expressed by triads is 55% or more, preferably 56% or more, and more preferably 57% or more. If the syndiotacticity (rr) expressed by triads is 55% or more, there is a tendency that the glass transition temperature (Tg) of the methacrylic resin becomes higher and the heat resistance is improved. The upper limit of the syndiotacticity (rr) is not particularly limited, but from the viewpoint of the molding temperature, the toughness of the molded body, and the secondary processability, it is preferably 67% or less, more preferably 65% or less, and further preferably 63% or less.
[0050] Syndiotacticity (rr) is the ratio of two chains (diads) of a chain of three consecutive structural units (triads) that are both racemic (rr). It should be noted that in the chains (diads) of structural units in polymer molecules, the same stereo configuration is called meso, and the opposite is called racemo, which are expressed as m and r, respectively.
[0051] The syndiotacticity (rr) can be calculated as described in the Examples below: The syndiotacticity (rr) is measured in deuterated chloroform at 22°C and 16 accumulation times. 1 H-NMR spectrum, from which the area (X) of the region of 0.60 to 0.95 ppm and the area (Y) of the region of 0.60 to 1.25 ppm when tetramethylsilane (TMS) was set to 0 ppm were measured, and calculated using the formula (X / Y)×100.
[0052] In addition, the glass transition temperature (Tg) of the methacrylic resin described in this embodiment is preferably 120° C. or higher, more preferably 122° C. or higher, and further preferably 124° C. or higher. The upper limit of the glass transition temperature (Tg) is not particularly limited, but is preferably 135° C. or lower, and may be 130° C. or lower, from the viewpoint of the molding temperature and the secondary processability of the molded body.
[0053] The glass transition temperature (Tg) in this specification is a midpoint glass transition temperature obtained from a DSC curve, and is measured by the method described in Examples below.
[0054] It should be noted that the syndiotacticity (rr) and glass transition temperature (Tg) of the methacrylic resin can be controlled by adjusting the polymerization temperature when synthesizing the methacrylic resin. For example, lowering the polymerization temperature is preferred for increasing the syndiotacticity (rr) of the methacrylic resin and increasing the glass transition temperature (Tg). In addition, the glass transition temperature (Tg) can also be controlled by adjusting the molecular weight of the methacrylic resin.
[0055] In addition, the methacrylic resin according to the present embodiment has a 5% weight loss temperature of 300° C. or higher and has excellent thermal stability.
[0056] Generally, when manufacturing a resin with a large molecular weight, a method of reducing the amount of chain transfer agent and / or polymerization initiator is adopted. However, when a thiol compound is used as a chain transfer agent, for example, the proportion of the growth free radicals that stop due to hydrogen abstraction reaction from the chain transfer agent becomes less, and relatively speaking, a large amount of polymers with double bond ends are easily generated by the disproportionation termination reaction of the growth free radicals. It is known that the terminal double bond undergoes thermal decomposition at a lower temperature than the main chain of the methacrylic resin (for example, T.Kashiwagi, et al., Macromolecules, 1986, 19, p.2160-2168, etc.), which becomes a cause of deterioration of the thermal stability of the resin. In this regard, the methacrylic resin described in this embodiment reduces the proportion of terminal double bonds by adjusting the ratio of the chain transfer agent amount to the polymerization initiator amount during manufacturing to an appropriate range. As a result, the methacrylic resin described in this embodiment can still have a 5% weight loss temperature of 300°C or above despite being a high molecular weight with a weight average molecular weight (Mw) of more than 400,000.
[0057] The 5% weight loss temperature in this specification is a temperature obtained from a thermogravimetric curve and is measured by the method described in the examples described later.
[0058] In the methacrylic resin according to the present embodiment, from the viewpoint of making the 5% weight loss temperature 300° C. or higher, the ratio of terminal double bonds to structural units derived from methyl methacrylate is preferably less than 0.015 mol %, more preferably less than 0.010 mol %, and even more preferably less than 0.006 mol %.
[0059] The methacrylic resin described in this embodiment can be manufactured by free radical polymerization as shown in the manufacturing method described later. The methacrylic resin manufactured by free radical polymerization contains terminal double bonds generated by disproportionation termination reaction in polymerization, hydrogen abstraction reaction of monomers based on polymerization initiator, etc. As mentioned above, the terminal double bonds will affect the thermal stability of the resin, so it is preferred that the proportion is small. The proportion of terminal double bonds is controlled by the method described later. If it can be reduced to less than 0.015 mol%, there is a tendency that the thermal stability of the methacrylic resin is greatly improved. It should be noted that the lower limit of the proportion of terminal double bonds is preferably 0 mol%, and can be 0.001 mol%.
[0060] The ratio of the terminal double bond to the structural unit derived from methyl methacrylate can be calculated as described in the Examples below: The ratio of the terminal double bond to the structural unit derived from methyl methacrylate can be calculated as follows ... 1H-NMR spectrum, from which the total area (X) of the peaks derived from the terminal double bonds of the methacrylic resin (5.47 to 5.52 ppm and 6.21 ppm) and the area (Y) of the peak derived from the α-methyl group of the methacrylic resin (0.5 to 1.25 ppm) were measured, and calculated using the formula [(3×X) / (2×Y)]×100.
[0061] It should be noted that the proportion of terminal double bonds in the methacrylic resin can be controlled by adjusting the amounts of the polymerization initiator and chain transfer agent used, the polymerization temperature, the polymerization time, etc. when synthesizing the methacrylic resin. For example, reducing the amount of the polymerization initiator, increasing the amount of the chain transfer agent, lowering the polymerization temperature, and extending the polymerization time are preferred for reducing the proportion of terminal double bonds.
[0062] Furthermore, the methacrylic resin according to the present embodiment preferably includes a terminal structure represented by the following formula (1) derived from a polymerization initiator.
[0063]
[0064] (Where R 1 , R 2 and R 3 Each independently represents an alkyl group, a substituted alkyl group, an ester group or an amide group. 1 , R 2 and R 3 At least one of represents an ester group or an amide group. 1 , R 2 and R 3 The two of them may be bonded to each other to form an alicyclic structure. * represents a connecting bond to a structural unit derived from a monomer. )
[0065] Examples of the alkyl group include linear or branched alkyl groups having 1 to 6 carbon atoms. Examples of the substituent group that the alkyl group may have include a hydroxyl group, a carboxyl group, an alkoxy group, and a halogen atom.
[0066] Examples of the ester group include -COOR 4 The group shown. 4 It represents an alkyl group having 1 to 6 carbon atoms, which may have a substituent such as a hydroxyl group, a carboxyl group, an alkoxy group or a halogen atom.
[0067] Examples of the amide group include -C(O)NR 5 The group shown. 5 It represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group or an alkenyl group having 2 to 6 carbon atoms, and may have a substituent such as a hydroxyl group, a carboxyl group, an alkoxy group or a halogen atom.
[0068] The terminal structure represented by the above formula (1) can be introduced into the molecule of the methacrylic resin by using a non-nitrile azo polymerization initiator represented by the following formula (2) when synthesizing the methacrylic resin. 1 , R 2 and R 3 The same meaning as in the above formula (1). By using such a non-nitrile azo polymerization initiator, the thermal stability of the obtained methacrylic resin tends to be improved compared to the case where a polymerization initiator other than the non-nitrile azo polymerization initiator (e.g., a nitrile azo polymerization initiator) is used. In addition, the non-nitrile azo polymerization initiator tends to have lower toxicity of the initiator itself and the decomposition product than the nitrile azo polymerization initiator, and is also preferred in this respect.
[0069]
[0070] Examples of the non-nitrile azo polymerization initiator represented by the formula (2) include 2,2'-azobis(isobutyric acid) dimethyl ester, 1,1'-azobis(cyclohexanecarboxylic acid methyl ester), 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide), 2,2'-azobis{2-methyl-N-[2-(1-hydroxyethyl)]propionamide}, and 2,2'-azobis{2-methyl-N-[2-(1-hydroxybutyl)]propionamide}. Among these, at least one selected from 2,2'-azobis(isobutyric acid) dimethyl ester and 1,1'-azobis(cyclohexanecarboxylic acid methyl ester) is preferred from the viewpoints of half-life temperature, cost, and the like.
[0071] The methacrylic resin described in this embodiment has the characteristics that the residual rate of the chain transfer agent is 0.005% by mass or less, and the proportion of the chain transfer agent remaining in the resin is small. The lower limit of the residual rate of the chain transfer agent is not particularly limited, and is preferably substantially 0% by mass (i.e., less than the detection limit). The residual rate of the chain transfer agent is measured by the method described in the examples described below.
[0072] The methacrylic resin described in the present embodiment not only has excellent heat resistance and thermal stability, but is also expected to be suitable for reuse, i.e., recycling, after being discarded. As a recycling method for methacrylic resins, for example, chemical recycling (a method of recovering decomposition oil in the form of decomposition products by thermal decomposition and reusing it as a chemical raw material or fuel) is known. In general, in order to improve the heat resistance and thermal stability of methacrylic resins, operations are performed to introduce a cyclic structure into the molecular structure of the methacrylic resin or to copolymerize monomers having a rigid structure. However, these structures will become impurities for chemical recycling, so they are not preferred. In this regard, it can be predicted that the proportion of structural units derived from methyl methacrylate in the methacrylic resin described in the present embodiment is high, and the yield of monomers recovered in the form of decomposition oil is high, and it can be expected to show good chemical recyclability.
[0073] <Method for producing methacrylic resin>
[0074] The method for producing the methacrylic resin described in the present embodiment includes: in the presence of a polymerization initiator and a chain transfer agent, a monomer mixture containing 98% by mass or more of methyl methacrylate is polymerized at a temperature lower than 100° C. until the polymerization conversion rate reaches 90% or more and the residual rate of the chain transfer agent reaches 0.005% by mass or less. As the method for producing the methacrylic resin, an existing known polymerization method can be used, and free radical polymerization methods such as continuous bulk polymerization, solution polymerization, emulsion polymerization, emulsifier-free (soap-free) emulsion polymerization, and suspension polymerization can be used. Among them, from the viewpoints of the structural design freedom, polymerization simplicity, productivity, etc. of the methacrylic resin, it is preferably a method for producing water-based polymerization, more preferably suspension polymerization and emulsion polymerization, and further preferably suspension polymerization.
[0075] [Suspension polymerization method]
[0076] In the suspension polymerization method, the methacrylic resin is synthesized in an aqueous suspension mixed with water, a monomer mixture, a dispersant, a polymerization initiator, a chain transfer agent, and optionally other additives. The order in which the components are mixed is not particularly limited. For example, the components can be mixed simultaneously to prepare an aqueous suspension. Alternatively, after mixing water, a polymerization initiator, and optionally other additives to prepare an aqueous solution, a monomer mixture and a chain transfer agent are added, followed by the addition of a dispersant to prepare an aqueous suspension. The mass ratio of the resulting methacrylic resin to water (methacrylic resin / water) is preferably 1.0 / 0.6 to 1.0 / 3.0.
[0077] As the monomer mixture, a mixture having a methyl methacrylate content of 98% by mass or more, preferably 99% by mass or more, more preferably 100% by mass is used.
[0078] As dispersants, there can be listed, for example, poorly water-soluble inorganic salts such as tricalcium phosphate, magnesium pyrophosphate, hydroxyapatite, kaolin, etc.; water-soluble polymers such as polyvinyl alcohol, methylcellulose, polyacrylamide, polyvinyl pyrrolidone, etc. When using poorly water-soluble inorganic salts as dispersants, it is effective to use anionic surfactants such as sodium α-olefin sulfonate and sodium dodecylbenzene sulfonate in combination. These dispersants can be added during the polymerization process as needed.
[0079] As the polymerization initiator, a known polymerization initiator such as an azo polymerization initiator and a peroxide polymerization initiator can be used. Among the known polymerization initiators, an azo polymerization initiator is preferred from the viewpoint of improving the thermal stability of the obtained methacrylic resin.
[0080] It is known that the free radicals generated by the polymerization initiator, in addition to the addition reaction to the monomer, also undergo a hydrogen abstraction reaction in the presence of a substance that easily provides hydrogen. In this regard, since the azo polymerization initiator only generates alkyl radicals, the hydrogen abstraction ability is lower than that of the peroxide polymerization initiator. Here, if the hydrogen abstraction ability of the polymerization initiator is high, then, for example, when methyl methacrylate is used as a monomer, the free radicals generated by the polymerization initiator are used to extract hydrogen from the α-methyl group of methyl methacrylate and the methyl group of the ester, and the free radicals on the newly generated α-methyl group and the methyl group of the ester are polymerized, and as a result, it is easy to generate a polymer with double bonds from the monomer structure remaining at the end. Therefore, when a polymerization initiator with high hydrogen abstraction ability is used, there is a tendency that the thermal stability of the obtained methacrylic resin is insufficient. Therefore, in order to obtain a methacrylic resin with high thermal stability, an azo polymerization initiator is more suitable than a peroxide polymerization initiator.
[0081] The hydrogen abstraction ability of the polymerization initiator can be measured by, for example, a radical trapping method using an α-methylstyrene dimer (ie, an α-methylstyrene dimer trapping method).
[0082] In addition, the inventors of the present invention have conducted research using various polymerization initiators, and found that compared with methacrylic resins synthesized using polymerization initiators other than non-nitrile azo polymerization initiators (e.g., nitrile azo polymerization initiators), the terminal structure introduced into the molecule of methacrylic resins synthesized using non-nitrile azo polymerization initiators is thermally stable. Therefore, among azo polymerization initiators, non-nitrile azo polymerization initiators are more preferred. As non-nitrile azo polymerization initiators, for example, substances represented by the above formula (2) can be listed, and from the viewpoints of half-life temperature, cost, etc., at least one selected from 2,2'-azobis(isobutyric acid)dimethyl ester and 1,1'-azobis(cyclohexanecarboxylic acid methyl ester) is preferred.
[0083] The amount of the polymerization initiator is preferably less than 1 part by mass, more preferably less than 0.5 parts by mass, and further preferably less than 0.1 parts by mass relative to 100 parts by mass of the total amount of the monomer mixture. The lower limit of the amount of the polymerization initiator is not particularly limited, but from the viewpoint of polymerization rate, it is preferably more than 0.001 parts by mass relative to 100 parts by mass of the total amount of the monomer mixture.
[0084] Examples of the chain transfer agent include primary alkyl mercaptan chain transfer agents such as n-butyl mercaptan, n-octyl mercaptan, n-hexadecyl mercaptan, n-dodecyl mercaptan, and n-tetradecyl mercaptan; secondary alkyl mercaptan chain transfer agents such as sec-butyl mercaptan and sec-dodecyl mercaptan; tertiary alkyl mercaptan chain transfer agents such as tert-dodecyl mercaptan and tert-tetradecyl mercaptan; thioglycolates such as 2-ethylhexyl thioglycolate, ethylene glycol dimercaptoacetate, trimethylolpropane tris(thioglycolate), and pentaerythritol tetra(thioglycolate); thiophenol, tetraethylthiuram disulfide, pentanephenylethane, acrolein, methacrolein, allyl alcohol, carbon tetrachloride, vinyl bromide, styrene oligomers (α-methylstyrene dimer, etc.), terpinolene, etc. These chain transfer agents may be used alone or in combination of two or more.
[0085] Among these chain transfer agents, from the viewpoints of handling properties, stability, thermal stability of the resulting methacrylic resin, etc., alkylthiol chain transfer agents and thioglycolates are preferred. As the alkylthiol chain transfer agent, n-octyl mercaptan is more preferred, and as the thioglycolate, 2-ethylhexyl thioglycolate is more preferred.
[0086] The amount of the chain transfer agent used is 0.03 mol% or less, preferably 0.025 mol% or less, based on the total amount of the monomer mixture. The lower limit of the amount of the chain transfer agent used is not particularly limited, but is preferably 0.005 mol% or more based on the total amount of the monomer mixture.
[0087] In order to obtain a methacrylic resin having a high weight average molecular weight (Mw) and a small proportion of terminal double bonds, the ratio of the total molar amount of the chain transfer agent to the total molar amount of the polymerization initiator is 1.6 or less. The ratio of the total molar amount of the chain transfer agent to the total molar amount of the polymerization initiator is preferably 1.5 or less, more preferably 1.0 or less. The lower limit of the ratio of the total molar amount of the chain transfer agent to the total molar amount of the polymerization initiator is not particularly limited, and is preferably 0.3 or more, for example.
[0088] From the viewpoint of controlling the syndiotacticity of the obtained methacrylic resin and productivity, the polymerization temperature during the synthesis of the methacrylic resin is lower than 100° C., preferably 20° C. or higher and lower than 100° C., more preferably 30 to 98° C., further preferably 50 to 96° C., and particularly preferably 60 to 95° C. After the main reaction is completed in the first stage polymerization, the temperature may be raised to a higher temperature than the first stage to carry out post-polymerization in order to reduce residual monomers.
[0089] It should be noted that, in order to initiate polymerization with a small amount of polymerization initiator, the polymerization reaction is preferably carried out by reducing the amount of dissolved oxygen. The amount of dissolved oxygen in the polymerization raw material is preferably less than 10ppm, more preferably less than 5ppm, further preferably less than 4ppm, and particularly preferably less than 2ppm. By making the amount of dissolved oxygen in this range, there is a tendency that the polymerization reaction is carried out smoothly and the coloring of the molded body of the methacrylic resin is suppressed. As a method for removing dissolved oxygen in the polymerization raw material, for example, inert gases such as nitrogen are continuously conveyed to the reaction vessel before, during and after the temperature is raised to the specified polymerization temperature. In order to remove dissolved oxygen from the raw materials added during the polymerization process, it is preferred that inert gases are also separately introduced into these raw materials.
[0090] In order to smoothly carry out the polymerization reaction, when the monomer mixture contains a polymerization inhibitor, it is preferred to remove the polymerization inhibitor in advance by distillation, alkali extraction or using an adsorbent such as alumina, silica gel, molecular sieve, activated carbon, ion exchange resin, zeolite, acid clay, etc.
[0091] In order to remove the dispersant, the suspension containing the methacrylic resin obtained by suspension polymerization may be subjected to a cleaning operation such as acid cleaning, water cleaning, or alkali cleaning. The number of times these cleaning operations are performed can be selected to be the optimal number considering the work efficiency and the removal efficiency of the dispersant, and may be once or multiple times.
[0092] As a method for separating the methacrylic resin from the suspension containing the methacrylic resin, a conventionally known dehydration method can be adopted, for example, a method using a centrifuge, a method of removing water by suction on a porous belt or a filtration membrane, etc.
[0093] The methacrylic resin in a water-containing state obtained by the above dehydration can be dried and recovered by a conventionally known method. Examples of drying methods include hot air drying in which hot air is sent from a hot air blower, a blast heater, etc. to the tank for drying; vacuum drying in which the system is depressurized and then heated as needed for drying; drum drying in which the obtained methacrylic resin is rotated in a container to disperse water; and spin drying in which the methacrylic resin is dried using centrifugal force. These drying methods may be implemented alone or in combination of two or more.
[0094] [Emulsion polymerization method]
[0095] In the emulsion polymerization method, a methacrylic resin is synthesized in an emulsion in which water, a monomer mixture, an emulsifier, a polymerization initiator, a chain transfer agent, and optionally other additives are mixed.
[0096] As the monomer mixture, a mixture having a methyl methacrylate content of 98% by mass or more, preferably 99% by mass or more, more preferably 100% by mass is used.
[0097] Examples of emulsifiers include anionic surfactants such as alkyl sulfonates, alkylbenzene sulfonates, dialkyl sulfosuccinates, α-olefin sulfonates, naphthalene sulfonate-formaldehyde condensates, alkylnaphthalene sulfonates, N-methyl-N-acyltaurates, phosphate ester salts (polyoxyethylene alkyl ether phosphates, etc.); nonionic surfactants, etc. In addition, examples of the above-mentioned salts include lithium salts, sodium salts, potassium salts, calcium salts, magnesium salts, etc. These emulsifiers may be used alone or in combination of two or more. It should be noted that the emulsifier used in the emulsion polymerization may remain in the final methacrylic resin.
[0098] When the pH of the emulsion deviates from neutrality and becomes acidic or alkaline, an appropriate pH adjuster may be used to prevent hydrolysis of methyl methacrylate as a monomer or a structural unit derived from methyl methacrylate in a methacrylic resin obtained by polymerization. Examples of the pH adjuster include boric acid-potassium chloride-potassium hydroxide, potassium dihydrogen phosphate-sodium hydrogen phosphate, boric acid-potassium chloride-potassium carbonate, citric acid-potassium hydrogen citrate, potassium dihydrogen phosphate-boric acid, and sodium dihydrogen phosphate-citric acid.
[0099] Examples of the polymerization initiator and the chain transfer agent include the same polymerization initiators and chain transfer agents as those in the above-mentioned suspension polymerization method. The polymerization initiator may be combined with a redox system as necessary.
[0100] In order to obtain a methacrylic resin having a high weight average molecular weight (Mw) and a small proportion of terminal double bonds, the ratio of the total molar amount of the chain transfer agent to the total molar amount of the polymerization initiator is 1.6 or less. The ratio of the total molar amount of the chain transfer agent to the total molar amount of the polymerization initiator is preferably 1.5 or less, more preferably 1.0 or less. The lower limit of the ratio of the total molar amount of the chain transfer agent to the total molar amount of the polymerization initiator is not particularly limited, and is preferably 0.3 or more, for example.
[0101] The methacrylic resin in solid or powdered form can be obtained by subjecting the latex of the methacrylic resin obtained by emulsion polymerization to heat drying or spray drying, or by subjecting it to a known method (adding a water-soluble electrolyte such as a salt or an acid to solidify it, and then separating the resin component from the aqueous phase after heat treatment to dry it, etc.). The above-mentioned salt is not particularly limited, and is preferably a divalent salt. Specifically, calcium salts such as calcium chloride and calcium acetate; magnesium salts such as magnesium chloride and magnesium sulfate, etc. can be listed. Among these salts, magnesium salts such as magnesium chloride and magnesium sulfate are preferred. During solidification, commonly added additives such as antioxidants and ultraviolet absorbers can be added.
[0102] Before the coagulation operation, the latex is preferably filtered using a filter, a mesh, etc. to remove fine polymerized scales in advance. This can reduce fish eyes, foreign matter, etc. caused by fine polymerized scales when the methacrylic resin is molded.
[0103] In this embodiment, the methacrylic resin obtained by aqueous polymerization may be in the form of a powder, a granule, or a powder and granule containing both powder and granule. Regarding the primary particles constituting the powder, granule, and powder and granule, suspension polymerization is suitable when producing primary particles with an average particle size of about 10 to 1000 μm, and emulsion polymerization is suitable when producing primary particles with an average particle size of about 50 to 500 nm. The powder, granule, and powder and granule may contain an aggregate of the above primary particles, i.e., an aggregate.
[0104] After the polymerization is completed, the methacrylic resin may be purified as needed. Examples of the purification method include: a method in which the methacrylic resin is dissolved in a solvent and then added dropwise to a poor solvent to precipitate the methacrylic resin; a method in which the methacrylic resin is heated to volatilize and remove impurities. These methods are appropriately selected according to the application and may be combined.
[0105] <Resin composition>
[0106] The resin composition according to this embodiment contains the methacrylic resin according to the above-mentioned embodiment.
[0107] The resin composition according to the present embodiment preferably contains multilayered polymer particles from the viewpoint of further improving the thermal stability and mechanical properties of the obtained molded article. The multilayered polymer particles are not particularly limited, and known particles can be used as appropriate.
[0108] When the resin composition described in this embodiment contains multilayer structure polymer particles, the blending ratio of the methacrylic resin and the multilayer structure polymer particles varies depending on the use of the molded body, etc., and the blending amount of the methacrylic resin is preferably 30 to 98 parts by mass, and the blending amount of the multilayer structure polymer particles is preferably 2 to 70 parts by mass, relative to 100 parts by mass of the total blending amount of the two components.
[0109] The resin composition described in this embodiment may also contain known additives such as light stabilizers, ultraviolet absorbers, heat stabilizers, matting agents, light diffusers, colorants, dyes, pigments, antistatic agents, heat ray reflective materials, lubricants, plasticizers, stabilizers, flame retardants, mold release agents, polymer processing aids, fillers, etc.; resins other than methacrylic resins. As resins other than methacrylic resins, for example, styrene resins such as acrylonitrile styrene resins and styrene maleic anhydride resins; polycarbonate resins; polyvinyl acetal resins; acylated cellulose resins; fluorine resins such as polyvinylidene fluoride and polyfluoroalkyl (meth)acrylate resins; silicone resins; polyolefin resins; polyethylene terephthalate resins; polybutylene terephthalate resins, etc.
[0110] In addition, in order to adjust the oriented birefringence of the molded body, the resin composition described in this embodiment may contain inorganic fine particles with birefringence described in Japanese Patent No. 3648201, Japanese Patent No. 4336586, etc., and low molecular weight compounds with birefringence and a molecular weight of 5,000 or less (preferably 1,000 or less) described in Japanese Patent No. 3696649.
[0111] The form of the resin composition according to the present embodiment is not particularly limited, and may be a powder, may be a granular form, may be a powder or granular form including both a powder and a granular form, or may be a pellet form.
[0112] <Paint (dope)>
[0113] The coating according to this embodiment contains the methacrylic resin and a solvent described in the above embodiment, and is used to manufacture a resin film by a solution casting method. The solvent contains a first solvent having a hydrogen bonding term δH of 1 to 12 in the Hansen solubility parameter and a second solvent having a hydrogen bonding term δH of 14 to 24. The coating according to this embodiment may also contain other components such as multilayer structure polymer particles, similarly to the resin composition described in the above embodiment. Each component such as the methacrylic resin and the multilayer structure polymer particles is dissolved or dispersed in the solvent.
[0114] Examples of the first solvent having a hydrogen bonding term δH of 1 to 12 include 1,4-dioxane (9.0), 2-phenylethanol (11.2), acetone (7.0), acetonitrile (6.1), chloroform (5.7), dibasic acid esters (8.4), diacetone alcohol (10.8), N,N-dimethylformamide (11.3), dimethyl sulfoxide (10.2), ethyl acetate (7.2), γ-butyrolactone (7.4), methyl ethyl ketone (5.1), methyl isobutyl ketone (4.1), dichloromethane (7.1), n-butyl acetate (6.3), N-methyl-2-pyrrolidone (7.2), propylene carbonate (4.1), 1,1,2,2-tetrachloroethane (5.3), tetrahydrofuran (8.0), and toluene (2.0). The numbers in parentheses represent the values of the hydrogen bonding term δH. These first solvents may be used alone or in combination of two or more. Among these first solvents, methyl ethyl ketone, chloroform, and dichloromethane are preferred, and dichloromethane is more preferred, from the viewpoint of excellent solubility of the methacrylic resin and high volatilization rate.
[0115] As the second solvent having a hydrogen bonding term δH of 14 to 24, for example, methanol (22.3), ethanol (19.4), isopropanol (16.4), butanol (15.8), ethylene glycol monoethyl ether (14.3) and the like can be cited. It should be noted that the numbers in the parentheses represent the values of the hydrogen bonding term δH. These second solvents can be used alone or in combination of two or more. Among these second solvents, methanol and ethanol are preferred, and ethanol is more preferred.
[0116] The ratio of the first solvent contained in the solvent is preferably 55 to 95% by mass, more preferably 60 to 95% by mass, and even more preferably 70 to 95% by mass.
[0117] The content of the methacrylic resin in the coating material according to the present embodiment is not particularly limited, and can be appropriately determined in consideration of the solubility of the methacrylic resin in the solvent used, the implementation conditions of the solution casting method, etc. The content of the methacrylic resin is preferably 5 to 50% by mass, more preferably 10 to 45% by mass, and further preferably 15 to 40% by mass.
[0118] The viscosity of the coating described in this embodiment can be appropriately adjusted by adjusting the content of the methacrylic resin and other components in the coating. From the viewpoint of coating properties, filtration accuracy, etc., the viscosity of the coating is preferably 1,000 poise (=100 Pa·s) or less, more preferably 500 poise (=50 Pa·s) or less, and further preferably 300 poise (=30 Pa·s) or less. It should be noted that the viscosity of the coating can be measured by the method described in the examples described below.
[0119] The coating described in this embodiment is used to manufacture a resin film by a solution casting method. When a resin film is manufactured by a solution casting method, first, the coating described in this embodiment is cast onto the surface of a support, and is applied into a uniform film using an applicator to form a coating. Alternatively, a pressure mold can be used to cast the coating onto a support. Then, the formed coating is heated on the support to evaporate the solvent to form a resin film. The conditions for evaporating the solvent can be appropriately determined according to the boiling point of the solvent used. And, the formed resin film is peeled off from the surface of the support. It should be noted that the obtained resin film can be appropriately provided for a drying process, a heating process, a stretching process, etc.
[0120] <Resin film>
[0121] The resin film according to this embodiment includes the methacrylic resin according to this embodiment. The resin film according to this embodiment is produced by, for example, a solution casting method using the coating material according to this embodiment.
[0122] The thickness of the resin film described in this embodiment is, for example, preferably 500 μm or less, more preferably 300 μm or less, and further preferably 200 μm or less. In addition, the thickness of the resin film described in this embodiment is, for example, preferably 10 μm or more, more preferably 30 μm or more, further preferably 50 μm or more, and particularly preferably 60 μm or more. If the thickness of the resin film is within the above range, there is an advantage that the resin film is not easily deformed when vacuum forming is performed using the resin film, and it is not easy to break in the deep drawing portion. Furthermore, there is also an advantage that the optical properties are uniform and a resin film with good transparency can be manufactured.
[0123] The total light transmittance of the resin film according to this embodiment is preferably 85% or more, more preferably 88% or more, and further preferably 90% or more. If the total light transmittance is within the above range, the transparency is high and thus it can be applied to optical applications requiring light transmittance.
[0124] The glass transition temperature of the resin film according to this embodiment is preferably 110° C. or higher, more preferably 115° C. or higher, further preferably 120° C. or higher, and particularly preferably 124° C. or higher. When the glass transition temperature is within the above range, the heat resistance of the resin film becomes sufficient.
[0125] The haze of the resin film described in this embodiment is preferably 2.0% or less, more preferably 1.5% or less, further preferably 1.3% or less, and particularly preferably 1.0% or less. In addition, the internal haze of the resin film is preferably 1.5% or less, more preferably 1.0% or less, further preferably 0.5% or less, and particularly preferably 0.4% or less. If the haze and internal haze are within the above ranges, the transparency is high, and therefore, it can be applied to optical applications requiring light transmittance. It should be noted that the haze includes the haze inside the film and the haze on the surface (outside) of the film, which are expressed as internal haze and external haze, respectively.
[0126] The YI (Yellow Index) of the resin film according to the present embodiment is preferably 1.2 or less, and more preferably 1.0 or less. When the YI is within the above range, the transparency is high and thus the film can be suitably used in optical applications requiring light transmittance.
[0127] The resin film described in the present embodiment preferably has excellent mechanical properties, for example, high bending resistance. As a method for evaluating bending resistance, the MIT bending test and the clamshell bending test are known. The number of bends until the resin film described in the present embodiment breaks in, for example, a clamshell bending test is preferably 6,000 times or more, more preferably 10,000 times or more. If the number of bends until the break is within the above range, the bending resistance of the resin film becomes sufficient. It should be noted that the number of bends until the break in the clamshell bending test is measured by the method described in the examples described later.
[0128] The resin film described in the present embodiment can be suitably used as an optical film such as a polarizer protective film. When the resin film described in the present embodiment is used as a polarizer protective film, the optical anisotropy is preferably small. It is particularly preferred that not only the optical anisotropy of the in-plane direction (length direction, width direction) of the resin film is small, but also the optical anisotropy of the thickness direction is small. In other words, it is preferred that the absolute values of the in-plane phase difference and the thickness direction phase difference are both small. For example, when the measurement wavelength is set to 590nm, the absolute value of the in-plane phase difference is preferably less than 20nm, more preferably less than 15nm. In addition, the absolute value of the thickness direction phase difference is preferably less than 50nm, more preferably less than 20nm, and further preferably less than 15nm.
[0129] Phase difference is an index value calculated based on birefringence. The in-plane phase difference (Re) and the thickness direction phase difference (Rth) can be calculated using the following formulas. In an ideal resin film that is completely optically isotropic in three dimensions, the in-plane phase difference Re and the thickness direction phase difference Rth are both 0.
[0130] Re=(nx-ny)×d
[0131] Rth=〔(nx+ny) / 2-nz〕×d
[0132] In the above formula, nx, ny and nz represent the refractive index of each axial direction when the in-plane extension direction (orientation direction of the polymer chain) is set as the X axis, the direction perpendicular to the X axis is set as the Y axis, and the thickness direction of the resin film is set as the Z axis. In addition, d represents the thickness of the resin film, and nx-ny represents the orientation birefringence. It should be noted that the MD direction of the film is set as the X axis, and in the case of a stretched film, the stretching direction is set as the X axis.
[0133] The orientation birefringence value of the resin film according to this embodiment is preferably -5.0×10 -4 ~5.0×10 -4 , more preferably -4.0×10 -4 ~4.0×10 -4 , more preferably -3.8×10 -4 ~3.8×10 -4 When the orientation birefringence is within the above range, birefringence does not occur during molding, and there is a tendency that stable optical characteristics can be obtained.
[0134] (Stretch)
[0135] The resin film according to this embodiment may be further stretched. By stretching the resin film, the mechanical strength of the resin film and the film thickness accuracy can be improved.
[0136] When the resin film described in the present embodiment is stretched, the coating described in the present embodiment is temporarily formed into a resin film in an unstretched state, and then uniaxial stretching or biaxial stretching is performed. Alternatively, in the molding of the resin film, while performing the film forming and solvent degassing processes, a stretching operation is appropriately applied. Thus, a stretched film (uniaxially stretched film or biaxially stretched film) can be manufactured. The stretching in the film molding and the stretching after the film molding can be appropriately combined.
[0137] The stretch ratio of the stretched film is not particularly limited and is appropriately determined according to the mechanical strength, surface properties, thickness accuracy, etc. of the stretched film to be manufactured. Depending on the stretching temperature, the stretch ratio is usually preferably selected in the range of 1.1 to 5 times, more preferably in the range of 1.3 to 4 times, and further preferably in the range of 1.5 to 3 times. If the stretch ratio is within the above range, there is a tendency to significantly improve the mechanical properties of the film, such as elongation, tear propagation strength, and rubbing fatigue resistance.
[0138] (use)
[0139] The resin film described in this embodiment can be used for various purposes such as transportation machinery, solar cell components, civil engineering and construction components, daily necessities, electrical and electronic equipment, optical components, medical supplies, etc. In particular, the resin film described in this embodiment has excellent heat resistance and optical properties, and therefore can be used for optical purposes. As optical uses, for example, front panels (cover windows) of various display devices, diffusers, polarizer protective films, polarizer protective films, phase difference films, light diffusion films, optical isotropic films, etc. can be listed.
[0140] Among these, the resin film described in the present embodiment can be suitably used as a polarizer protective film or a front panel (cover window) of a display device. When the resin film described in the present embodiment is used as a front panel (cover window) of various display devices, a functional coating layer such as a primer layer and a hard coat layer can be formed on at least one main surface of the resin film as required. In addition, when the resin film described in the present embodiment is used as a polarizer protective film, the resin film described in the present embodiment is pasted with a polarizer to form a polarizing plate. The polarizer is not particularly limited, and any existing known polarizer can be used. The polarizing plate can be used in display devices such as liquid crystal display devices and organic EL display devices.
[0141] Example
[0142] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples, but the present invention is not limited to the following Examples. It should be noted that the measurement methods of various physical properties described in Examples and Comparative Examples are as follows.
[0143] (1) Polymerization conversion rate
[0144] The polymerization conversion rate of the methacrylic resin is determined from the ratio of the weight of the methacrylic resin obtained after washing with water and drying to the weight of the monomers used. The weight of the methacrylic resin obtained after washing with water and drying is the value obtained by subtracting the weight of the residual monomers in the methacrylic resin obtained by the following analysis.
[0145] (Analysis conditions of Example 1 and Example 2)
[0146] The methacrylic acid resin was measured using a nuclear magnetic resonance apparatus (AVANCE III 400 MHz, manufactured by Bruker) in a deuterated chloroform solution at 22°C and 16 accumulation times. 1 H-NMR spectrum. Based on this spectrum, the area (Y) of the peak derived from the methoxy group (3.60 ppm) and the area of the peak of the residual monomer (6.11 ppm and 5.56 ppm when the monomer is methyl methacrylate) are calculated. The ratio of the residual monomer is calculated using the formula [(3×X) / (2×Y)]×100, and the value is substituted into the pre-made 1 The polymerization conversion rate was calculated using the residual monomer ratio calculated by H-NMR and the residual monomer amount determined by gas chromatography.
[0147] (Analysis conditions of Example 3, Comparative Example 2 and Comparative Example 3)
[0148] A gas chromatograph (Agilent Technologies, 7890B) was used, and as the analytical column, DB-1 (Agilent Technologies, 0.8 μm film thickness × 0.20 mm inner diameter × 30 m length) was used, and the analysis was performed under the conditions of an injection port temperature of 150°C and a detector temperature of 320°C. The column temperature was set to the following conditions: the temperature was raised from 35°C to 210°C at a heating rate of 30°C / min, then from 210°C to 260°C at a heating rate of 10°C / min, and then from 260°C to 320°C at a heating rate of 20°C / min, and maintained for 3 minutes. A calibration curve was prepared by the internal standard method using chlorobenzene as an internal standard substance, and the polymerization conversion rate was calculated after calculating the residual amount of the monomer in the methacrylic resin.
[0149] (2) Residual rate of chain transfer agent
[0150] The residual rate of the chain transfer agent in the methacrylic resin was quantitatively determined using a gas chromatograph (manufactured by Agilent Technologies, 7890B). As the analytical column, DB-1 (manufactured by Agilent Technologies, film thickness 0.8 μm × inner diameter 0.20 mm × length 30 m) was used, the injection port temperature was set to 150°C, and the detector temperature was set to 320°C. The column temperature was set to the following conditions for analysis: the temperature was increased from 35°C to 210°C at a heating rate of 30°C / min, then from 210°C to 260°C at a heating rate of 10°C / min, and then from 260°C to 320°C at a heating rate of 20°C / min, and maintained for 3 minutes. Using dichloromethane as the measurement solvent and chlorobenzene as the internal standard substance, a calibration curve was prepared using the internal standard method to calculate the residual rate of the chain transfer agent in the methacrylic resin.
[0151] (3) Syndiotacticity expressed in triads (rr)
[0152] The methacrylic acid resin was measured using a nuclear magnetic resonance apparatus (AVANCE III 400 MHz, manufactured by Bruker) in a deuterated chloroform solution at 22°C and 16 accumulation times. 1 H-NMR spectrum. Based on the spectrum, the area (X) of the region of 0.60 to 0.95 ppm and the area (Y) of the region of 0.60 to 1.25 ppm when tetramethylsilane (TMS) is set to 0 ppm are measured, and then the syndiotacticity (rr) expressed by triads is calculated using the formula (X / Y)×100.
[0153] (4) Weight average molecular weight (Mw) and the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn)
[0154] The weight average molecular weight (Mw), number average molecular weight (Mn) and the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the methacrylic resin were calculated by a standard polystyrene conversion method using gel permeation chromatography (GPC). Specifically, a sample solution prepared by dissolving 20 mg of a methacrylic resin in 10 mL of tetrahydrofuran was used and the analysis was performed using the following apparatus and conditions.
[0155] Measuring machine: HLC-8220GPC (Tosoh Corporation)
[0156] Detector: RI detector
[0157] Solvent: Tetrahydrofuran
[0158] Guard column: TSKgel guardcolumn SuperHZ-H (Tosoh Corporation)
[0159] Analytical column: TSKgel SuperHZM-H × 2 (Tosoh Corporation)
[0160] Measurement temperature: 40℃
[0161] Standard material: Standard polystyrene (Tosoh Corporation)
[0162] (5) Ratio of terminal double bonds
[0163] About 20 mg of a methacrylic resin was dissolved in 0.6 to 0.7 mL of deuterated chloroform to prepare a solution, and a nuclear magnetic resonance apparatus (manufactured by Bruker, AVANCE NEO 700 MHz) was used to perform the analysis. 1 H-NMR measurement. The measurement temperature was set to 20°C, the number of accumulations was set to 8,192 times, and the ES method, which is one of the solvent elimination methods, was used to eliminate the peak of the methoxy group derived from the methacrylic resin (3.60 ppm, the value when the chemical shift of the peak of the solvent was set to 7.26 ppm). 1 The total area (X) of the peaks (5.47 to 5.52 ppm and 6.21 ppm) derived from the terminal double bond of the methacrylic resin and the area (Y) of the peak (0.5 to 1.25 ppm) derived from the α-methyl group of the methacrylic resin were measured by H-NMR spectrum, and then the ratio of the terminal double bond of the methacrylic resin was calculated by the formula [(3×X) / (2×Y)]×100.
[0164] (6) Glass transition temperature (Tg)
[0165] A differential scanning calorimeter (DSC; manufactured by Hitachi High-Technologies Corporation, DSC7000X) was used to measure the glass transition temperature (Tg) of the methacrylic resin and the resin film before stretching. First, the DSC measurement was performed under the following conditions: at a nitrogen flow rate of 40 mL / min, the temperature was raised from 40°C to 160°C at a heating rate of 10°C / min for the first heating, and after cooling to 40°C, the temperature was raised from 40°C to 160°C at a heating rate of 10°C / min for the second heating. And, based on the DSC curve measured during the second heating, the midpoint glass transition temperature (the intersection temperature of the straight line with the same distance in the longitudinal direction from the straight line obtained by extending the baseline before the inflection point toward the high temperature side and the straight line obtained by extending the baseline after the inflection point toward the low temperature side and the curve of the step-like change part of the glass transition) was read.
[0166] (7) 5% weight loss temperature (Td5)
[0167] The 5% weight loss temperature (Td5) of the methacrylic resin was measured using a thermogravimetric analyzer (manufactured by Hitachi High-Technologies Corporation, STA7200). The first temperature increase was performed from 40°C to 190°C at a temperature increase rate of 10°C / min under a nitrogen gas flow of 200 mL / min, thereby removing the moisture absorbed by the methacrylic resin, and then cooling to 40°C. Then, the temperature was increased from 40°C to 500°C at a temperature increase rate of 10°C / min for the second temperature increase. The temperature at which the sample lost 95% of its weight, obtained from the thermogravimetric (TG) curve measured during the second temperature increase, was set as the 5% weight loss temperature (Td5).
[0168] (8) Paint viscosity
[0169] A methacrylic resin was dissolved in a mixed solvent containing 93% by mass of dichloromethane and 7% by mass of ethanol to prepare a coating having a solid content concentration (SC) of 10% by mass (Example 1 and Example 2), 12% by mass (Example 3) or 25% by mass (Comparative Example 1 and Comparative Example 2). The coating viscosity was measured using a B-type viscometer (BMII, manufactured by Toki Sangyo Co., Ltd.). The temperature of the measurement sample was adjusted to 23°C, and a No. 2 rotor was used to read the indicated value at 30 rpm (12 rpm for Example 1 and Example 3).
[0170] (9) Haze measurement
[0171] The haze of the stretched resin film was measured using a haze meter (Suga Test Instruments, HZ-V3) in accordance with JIS K7136. In addition, the two sides of the resin film were sandwiched with glycerin and glass in sequence and the same measurement was performed, and the value obtained was set as the internal haze. The obtained result was converted into a value equivalent to a film thickness of 40 μm.
[0172] (10) Total light transmittance
[0173] The total light transmittance of the stretched resin film was measured using a haze meter (HZ-V3 manufactured by Suga Test Instruments) in accordance with JIS K7361-1.
[0174] (11)YI
[0175] The YI of the stretched resin film was measured using a spectrocolorimeter (manufactured by Suga Test Instruments, SC-P) in accordance with JIS K7373. The obtained result was converted into a value corresponding to a film thickness of 40 μm.
[0176] (12) Flip-top bending test
[0177] A clamshell-type tabletop durability tester (DMLHP-CS, manufactured by YUASA SYSTEM) was used to evaluate the bending resistance of the methacrylic resin film after stretching. The conditions were set as follows: at 23°C and a relative humidity of 55%, the radius of curvature was 0.35 mm, and the test speed was 30 r / min (30 times / min). The film was cut into short strips of 2 cm in width and 5 cm in length and used as a test piece. The test was conducted in a direction perpendicular to the stretching direction to produce creases. The test continued until the test piece broke. Each sample was tested 3 times, and the bending resistance was evaluated based on the number of times it broke.
[0178] <Example 1>
[0179] 170 parts by mass of deionized water, 0.10 parts by mass of disodium hydrogen phosphate as a suspension aid, and 0.037 parts by mass of 2,2'-azobis(isobutyric acid)dimethyl ester (V-601 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were placed in a 2-liter glass reactor equipped with a three-way backward blade stirrer. The aqueous solution in the reactor was stirred at 550 rpm while nitrogen (oxygen concentration was 0.2 ppm) was passed through to replace the air in the reactor. Then, a monomer solution containing 100 parts by mass of methyl methacrylate (MMA) and 0.017 parts by mass of n-octyl mercaptan (n-OM) as a chain transfer agent was added to the reactor. Next, 0.375 parts by mass of METOLOSE 60SH-50 (hydroxypropyl methylcellulose manufactured by Shin-Etsu Chemical Co., Ltd.), a water-soluble polymer, was added to the reactor as a dispersant. After that, after stirring for 30 minutes, the liquid temperature in the reactor was raised to 77°C to start polymerization. After the monomers were reacted at 77°C for 4 hours, the liquid in the reactor was heated to 95°C. The reaction solution was stirred at the same temperature for 1 hour to terminate the polymerization. The obtained resin was washed with deionized water in an amount 4.6 times the amount of the resin and dried to obtain bead-shaped particles. The particles were dissolved in dichloromethane in a concentration of 10% by mass, and the solution was added dropwise to 5 times the amount of methanol of the dichloromethane solution to precipitate the resin. The precipitated resin was recovered by suction filtration and dried to obtain a methacrylic resin after the precipitation was purified.
[0180] A mixed solvent containing 93% by mass of dichloromethane and 7% by mass of ethanol was added to the spiral tube container, and then the dried methacrylic resin was added. The solution was stirred until the methacrylic resin was completely dissolved to prepare a coating having a solid content concentration (SC) of 10% by mass.
[0181] The coating prepared above is cast on a PET film substrate (manufactured by Toyobo Co., Ltd., COSMOSHINE A4100) and applied into a uniform film using an applicator. At this time, the gap is adjusted so that the thickness after drying becomes about 60 μm. After coating, the coating is dried in an oven at 40°C for 1 hour, and then the resulting resin film is peeled off from the PET film substrate. Thereafter, the resin film is fixed on a stainless steel frame and dried in an oven at 140°C for 2 hours to remove the residual solvent, thereby obtaining a resin film. Furthermore, the resulting resin film is subjected to width-fixed uniaxial stretching at 135°C. The stretching ratio is set to 1.5 times, and the stretching speed is set to 100 mm / min. The average film thickness of the stretched resin film is 43 μm.
[0182] Table 1 shows the physical properties of the methacrylic resin, the coating material, and the resin film in Example 1.
[0183] <Example 2>
[0184] The same operation as in Example 1 was performed except that the amount of n-octyl mercaptan (n-OM) was changed to 0.036 parts by mass and the amount of deionized water used in washing the obtained resin was changed to 4.3 times the amount of the resin. The average film thickness of the obtained stretched resin film was 41 μm. The physical properties of the methacrylic resin, the coating, and the resin film in Example 2 are shown in Table 1.
[0185] <Example 3>
[0186] 150 parts by mass of deionized water, 0.400 parts by mass of tricalcium phosphate as a dispersant, 0.0075 parts by mass of sodium α-olefin sulfonate, and 0.30 parts by mass of sodium chloride were placed in a 4-liter glass reactor equipped with an H-type stirring blade type stirrer. The aqueous solution in the reactor was stirred at 250 rpm while nitrogen (oxygen concentration was 0.2 ppm) was passed to replace the air in the reactor. Then, a monomer solution containing 100 parts by mass of methyl methacrylate (MMA), 0.017 parts by mass of n-octyl mercaptan (n-OM) as a chain transfer agent, and 0.037 parts by mass of 2,2'-azobis(isobutyric acid) dimethyl ester (V-601 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator was added to the reactor. Thereafter, the liquid temperature in the reactor was raised to 80°C to start polymerization. After 45 minutes from the start of polymerization, 0.10 parts by mass of tricalcium phosphate was added to the reaction solution. After 2 hours from the start of polymerization, the temperature of the liquid in the reactor was raised to 95°C, and the moment of continuous stirring at 95°C for 1 hour was regarded as the end of polymerization. Relative to the amount of the monomer fed, acid washing was performed twice using 1N hydrochloric acid in an amount of 0.1 times the weight ratio, and water washing and drying were performed to obtain beaded resin particles. The particles were dissolved in dichloromethane in a concentration of 7% by mass, and the obtained dichloromethane solution was filtered with a pressure filter provided with a 5μm filter, and the filtrate containing the resin was dried in an oven at 70°C for 12 hours and at 140°C for 2 hours. The resin obtained after drying was immersed in methanol in an amount of 2.5 times the weight ratio of the resin, and was allowed to stand at room temperature for 12 hours and at 50°C for 5 hours. After the resin was recovered by suction filtration, it was dried in an oven at 70°C for 12 hours and at 140°C for 5 hours. Furthermore, the resin was vacuum-dried at 140° C. for 2 hours to obtain a purified methacrylic resin.
[0187] A mixed solvent containing 93% by mass of methylene chloride and 7% by mass of ethanol was added to the spiral tube container, and then the dried methacrylic resin was added. The solution was stirred until the methacrylic resin was completely dissolved to prepare a coating having a solid content concentration (SC) of 12% by mass.
[0188] The coating prepared above is cast on a PET film substrate (manufactured by Toyobo Co., Ltd., COSMOSHINE A4100) and applied into a uniform film using an applicator. At this time, the gap is adjusted so that the thickness after drying becomes about 60 μm. After coating, the coating is dried in an oven at 40°C for 1 hour, and then the obtained resin film is peeled off from the PET film substrate. Thereafter, the resin film is fixed on a stainless steel frame and dried in an oven at 140°C for 2 hours to remove the residual solvent, thereby obtaining a resin film. Furthermore, the obtained resin film is subjected to width-fixed uniaxial stretching at 132°C. The stretching ratio is set to 1.5 times, and the stretching speed is set to 100 mm / min. The average film thickness of the stretched resin film is 41 μm.
[0189] Table 1 shows the physical properties of the methacrylic resin, the coating material, and the resin film in Example 3.
[0190] <Comparative Example 1>
[0191] As a methacrylic resin, PARAPET HR-S (manufactured by Kuraray Co., Ltd., a copolymer of methyl methacrylate (MMA) and methyl acrylate (MA), MMA / MA=98.9 / 1.1 (mass ratio)) was used, and the precipitation purification of the methacrylic resin from a dichloromethane solution to methanol was not performed. Among them, precipitation purification was performed only when preparing a quantitative sample for terminal double bonds. Using this methacrylic resin, the solid content concentration (SC) of the coating was changed to 25% by mass, and the stretching temperature of the resin film was changed to 125°C. Except for this, the same operation as in Example 1 was performed. The average film thickness of the obtained stretched resin film was 36μm. The physical properties of the methacrylic resin, coating and resin film in Comparative Example 1 are shown in Table 1.
[0192] <Comparative Example 2>
[0193] 170 parts by mass of deionized water, 0.10 parts by mass of disodium hydrogen phosphate as a suspension aid, and 0.037 parts by mass of 2,2'-azobis(isobutyric acid)dimethyl ester (V-601 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were placed in a 2-liter glass reactor equipped with a three-way backward blade stirrer. The aqueous solution in the reactor was stirred at 550 rpm while nitrogen (oxygen concentration was 0.2 ppm) was passed through to replace the air in the reactor. Then, a monomer solution containing 100 parts by mass of methyl methacrylate (MMA) and 0.270 parts by mass of n-octyl mercaptan (n-OM) as a chain transfer agent was added to the reactor. Next, 0.375 parts by mass of METOLOSE 60SH-50 (hydroxypropyl methylcellulose manufactured by Shin-Etsu Chemical Co., Ltd.), a water-soluble polymer, was added to the reactor as a dispersant. After that, after stirring for 30 minutes, the liquid temperature in the reactor was raised to 79°C to start polymerization. After the monomers were reacted at 79°C for 6 hours, the liquid in the reactor was heated to 94°C. The reaction solution was stirred at the same temperature for 1 hour to terminate the polymerization. The obtained resin was washed with deionized water 3.4 times the amount of the resin and dried to obtain bead-shaped particles. The particles were dissolved in dichloromethane in a concentration of 10% by mass, and the solution was added dropwise to 5 times the amount of methanol of the dichloromethane solution to precipitate the resin. The precipitated resin was recovered by suction filtration and dried to obtain a methacrylic resin after the precipitation was purified.
[0194] A mixed solvent containing 93% by mass of dichloromethane and 7% by mass of ethanol was added to the spiral tube container, and then the dried methacrylic resin was added. The solution was stirred until the methacrylic resin was completely dissolved to prepare a coating having a solid content concentration (SC) of 25% by mass.
[0195] The coating prepared above is cast on a PET film substrate (manufactured by Toyobo Co., Ltd., COSMOSHINE A4100) and applied into a uniform film using an applicator. At this time, the gap is adjusted so that the thickness after drying becomes about 40 μm. After coating, the coating is dried in an oven at 40°C for 1 hour, and then the resulting resin film is peeled off from the PET film substrate. Thereafter, the resin film is fixed on a stainless steel frame and dried in an oven at 140°C for 2 hours to remove the residual solvent, thereby obtaining a resin film. Furthermore, the resulting resin film is subjected to width-fixed uniaxial stretching at 132°C. The stretching ratio is set to 1.5 times, and the stretching speed is set to 100 mm / min. The average film thickness of the stretched resin film is 38 μm.
[0196] Table 1 shows the physical properties of the methacrylic resin, the coating material, and the resin film in Comparative Example 2.
[0197] <Comparative Example 3>
[0198] 170 parts by mass of deionized water, 0.10 parts by mass of disodium hydrogen phosphate as a suspension aid, and 1.00 parts by mass of 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (V-70, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added to a 0.5-liter glass reactor equipped with an H-type stirring blade type stirrer. The aqueous solution in the reactor was stirred at 380 rpm while nitrogen (oxygen concentration was 0.2 ppm) was passed through, and after replacing the air in the reactor, 100 parts by mass of methyl methacrylate (MMA) was added to the reactor. Next, 0.375 parts by mass of METOLOSE 60SH-50 (hydroxypropylmethylcellulose, manufactured by Shin-Etsu Chemical Co., Ltd.), a water-soluble polymer as a dispersant, was added to the reactor. Thereafter, after stirring for 30 minutes, the liquid temperature in the reactor was raised to 30°C to start polymerization. After the monomer was reacted at 30°C for 3 hours, the liquid in the reactor was heated to 50°C and stirred for 1 hour, then heated to 70°C and stirred for 30 minutes, and then heated to 95°C and stirred for 1 hour, and the polymerization was completed. Relative to the obtained resin, 7 times the amount of deionized water was used to wash it, and it was dried to obtain bead-shaped particles. The particles were dissolved in dichloromethane in a concentration of 10% by mass, and the solution was added dropwise to 5 times the amount of methanol of the dichloromethane solution to precipitate the resin. The precipitated resin was recovered by suction filtration and dried to obtain a methacrylic resin after the precipitation was purified. The physical properties of the methacrylic resin in Comparative Example 3 are shown in Table 1.
[0199] [Table 1]
[0200]
[0201] As shown in Table 1, in Examples 1 to 3, the syndiotacticity is high, and as a result, a methacrylic resin having a high glass transition temperature (Tg) and a resin film containing the methacrylic resin can be obtained. In addition, in Examples 1 to 3, the weight average molecular weight (Mw) of the methacrylic resin is large, and therefore the resin film shows excellent bending resistance. Specifically, the stretched resin film of Example 1 does not break even if the number of bends exceeds 20,000 times, the stretched resin film of Example 2 does not break until the number of bends reaches 11,000 to 13,000 times, and the stretched resin film of Example 3 does not break even if the number of bends exceeds 20,000 times. Furthermore, in Examples 1 to 3, the 5% weight loss temperature (Td5) of the methacrylic resin shows a value exceeding 300°C. That is, Examples 1 to 3 are excellent in heat resistance (glass transition temperature (Tg)), thermal stability (5% weight loss temperature (Td5)), and mechanical properties (bending resistance) of the molded body.
[0202] On the other hand, in Comparative Example 1, although the 5% weight loss temperature (Td5) of the methacrylic resin was high, the syndiotacticity was low, and as a result, the glass transition temperature (Tg) of the methacrylic resin and the resin film was lower than that of Examples 1 to 3. In addition, in Comparative Example 1, the weight average molecular weight (Mw) of the methacrylic resin was small, and therefore, the mechanical properties of the resin film were inferior to those of Examples 1 to 3. Specifically, the number of bends until the resin film of Comparative Example 1 was broken after stretching was kept at 3,000 to 4,500 times.
[0203] In Comparative Example 2, the syndiotacticity is high, and as a result, a methacrylic resin and a resin film having a high glass transition temperature (Tg) can be obtained, and the 5% weight loss temperature (Td5) of the methacrylic resin is also high. However, the weight average molecular weight (Mw) of the methacrylic resin is small, and therefore, the mechanical properties of the resin film are inferior to those of Examples 1 to 3. Specifically, the number of bends until the resin film of Comparative Example 2 after stretching is kept at 1,000 to 2,000 times.
[0204] In Comparative Example 3, the syndiotacticity is high, and as a result, a methacrylic resin with a high glass transition temperature (Tg) can be obtained. However, since the methacrylic resin has a large proportion of terminal double bonds, the 5% weight loss temperature (Td5) is lower than 300°C, and the thermal stability is low.
Claims
1. A methacrylic resin, wherein The proportion of structural units derived from methyl methacrylate is 98% by mass or more, The weight average molecular weight (Mw) measured by gel permeation chromatography (GPC) is 400,000 or more, and the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) is 1.6 to 2.8, The syndiotacticity expressed as triad is 55% or more, 5% weight loss temperature is above 300℃, The residual ratio of the chain transfer agent is 0.005 mass % or less.
2. The methacrylic resin according to claim 1, comprising a terminal structure represented by the following formula (1) derived from a polymerization initiator, In formula (1), R 1 , R 2 and R 3 Each independently represents an alkyl group, a substituted alkyl group, an ester group or an amide group, wherein R 1 , R 2 and R 3 At least one of represents an ester group or an amide group, R 1 , R 2 and R 3 Two of them may be bonded to each other to form an alicyclic structure, and * represents a bond connecting to a structural unit derived from a monomer.
3. The methacrylic resin according to claim 1 or 2, wherein The ratio of the terminal double bonds to the structural units derived from methyl methacrylate is less than 0.015 mol %. The methacrylic resin according to claim 1 or 2, which has a glass transition temperature of 120°C or higher.
5. A method for producing a methacrylic resin, comprising: A polymerization step of polymerizing a monomer mixture containing 98% by mass or more of methyl methacrylate at a temperature lower than 100° C. in the presence of a polymerization initiator and a chain transfer agent until a polymerization conversion rate reaches 90% or more and a residual rate of the chain transfer agent reaches 0.005% by mass or less, The amount of the chain transfer agent used is 0.03 mol% or less relative to the total amount of the monomer mixture. The ratio of the total molar amount of the chain transfer agent to the total molar amount of the polymerization initiator is 1.6 or less.
6. The method for producing a methacrylic resin according to claim 5, wherein: The polymerization initiator is a non-nitrile azo polymerization initiator.
7. The method for producing a methacrylic resin according to claim 5 or 6, wherein: In the polymerization step, aqueous polymerization is performed.
8. A resin composition comprising the methacrylic resin according to claim 1 or 2, and optionally comprising multilayer structure polymer particles.
9. A coating material for producing a thin film by a solution casting method, comprising the methacrylic resin according to claim 1 or 2 and a solvent, The solvent comprises a first solvent having a hydrogen bonding term δH of 1-12 in Hansen solubility parameter and a second solvent having a hydrogen bonding term δH of 14-24. 10 . A resin film comprising the methacrylic resin according to claim 1 or 2 .
11. The resin film according to claim 10, wherein The number of bending times until fracture in the clamshell type bending test was 6,000 times or more. 12 . The resin film according to claim 10 , comprising multilayer structure polymer particles.
13. The resin film according to claim 10, wherein The resin film is a polarizer protective film. 14 . A polarizing plate comprising a polarizer and the resin film according to claim 10 laminated together. 15 . A display device comprising the polarizing plate according to claim 14 .
Citation Information
Patent Citations
Resin composition and dope for film manufacturing by solution casting method
WO2019167471A1